Analysis of combustion synthesis method for Cu/CeO2 synthesis by integrating thermodynamics and design of experiments approach - Parisa, Ebrahimi (2022)
Solution combustion synthesis (SCS) is a commonly used method for synthesizing nanomaterials due to its energy and time efficiency. Herein, we present an analysis of synthesis parameters to optimize a targeted property by integrating results from thermodynamic calculations with Design of Experiments (DOE) approach. The analysis is conducted on Cu/CeO2, a catalyst planned to be used for CO2 conversion reaction. The SCS reaction using Cu(NO3)2 and Ce(NO3)3 precursors as oxidizers and glycine (C2H5NO2) as a fuel were thermodynamically studied in detail to provide input parameters for DOE. Estimations of the adiabatic combustion temperature and product composition at the equilibrium conditions were accomplished on the basis of Gibbs free energy minimization principle. Two of the operative parameters in SCS; the fuel to oxidizer ratio (φ), and metal loading (Cu on CeO2); were optimized using the Central Composite Design approach (CCD) and the statistical software application Minitab. The analysis of combustion system was performed for two cases; without the excess external oxygen supply, and with excess oxygen presence. The results showed that the φ variable is the most significant factor effecting the adiabatic combustion temperature and total gaseous products. On the basis of 1 mol of solid product, the optimum predicted values to have the maximum adiabatic combustion temperature and maximum gas products for both the cases of without and with the use of excess oxygen being ∼1650 K, 15 mol and ∼2550 K and 30 mol, respectively.